288 A phase 1 study of IMC-001, a PD-L1 blocker, in patients with metastatic or locally advanced solid tumors. (9th November 2020) - Keam, Bhumsuk; Kim, Tae Min; Oh, Do-Youn; Ock, Chan-Young; Kang, Won Ki; Park, Yeon Hee; Lee, Jeeyun; Lee, Ji Hye; Song, Yun Jeong; Park, Young Suk
Abstract : Background: IMC-001 is a fully human IgG1 monoclonal antibody that binds to human PD-L1 and mediate the antibody-dependent cell-mediated cytotoxicity. The main objectives of this study were to evaluate the safety, pharmacokinetics, and pharmacodynamics of IMC-001 in patients with advanced solid tumors. Here, we report final result of the phase 1 study of IMC-001. Methods: This open-labeled phase 1 study used standard 3+3 dose-escalation design, dose ranging from 2 to 20 mg. IMC-001 was administered intravenously every two weeks until disease progression or unacceptable toxicity. Dose limiting toxicity (DLT) window was defined as 21 days from the first dose. Adverse events (AEs) were assessed using CTCAE v4.03, and tumor response was assessed by and the Response Evaluation Criteria In Solid Tumors (RECIST) version v1.1. Results: Fifteen subjects (8 Male, 7 Female; Median age : 58 [range 39–69]) were included in 5 dose escalation cohorts. No DLT was observed and the maximum tolerated dose was not reached. Most common AEs were general weakness, decreased appetite, fever, and cough. No Grade 4 or 5 treatment emergent AEs (TEAEs) were reported during the study and no TEAE or serious AE led to treatment discontinuation or death. There were no infusion-related reactions during this study. Grade 2 immune-induced thyroiditis and diabetes mellitus suspected to be related to IMC-001 were seen in one subject at 2 mg/kg cohort. Over the dose range of 2 to 20 mg/kg IMC-001, AUC 0-14d, AUC 0—∞, and Cmax generally appeared to increase in a dose proportional manner for each step of dose escalation. Of the 15 enrolled patients, one subject with colon cancer showed partial response, and disease control rate was 33.3%. There were total 3 biliary tract cancer patients (1 GB cancer, 2 Cholangiocarcinoma) who received ≥3 lines of systemic therapies prior to this trial. They all had stable disease during IMC-001 treatment, and one cholangiocarcinoma subject received the treatment for 434 days. Conclusions: IMC-001 demonstrated a favorable safety profile up to 20 mg/kg given IV every 2 weeks and showed encouraging preliminary efficacy in patients with advanced solid tumors. Based on PK and PD data, 20 mg/kg was selected as recommended Phase 2 dose (RP2D). Ethics Approval: This study was approved by Institutional Review Board; approval number SMC 2018-01-007-001 and H-1801-042-913.